(untitled) (Research, Society and Development, 2022)
The present study aims to report a series of clinical cases of endodontic treatment of maxillary and mandibular premolar teeth with three root canals, with the aid of magnification and modern operative techniques of endodontic therapy.The endodontic treatment of these teeth was based on a careful radiographic evaluation and the access was performed with the use of magnification, which allowed the location of the holes in the root canals and the conduction of the endodontic treatment. The chemical-mechanical preparation was performed with mechanized nickel-titanium instruments (X1-Blue) associated with 2.5% sodium hypochlorite irrigating solution. As an auxiliary protocol in the final cleaning, a passive ultrasonic irrigation (PUI) was performed. At the end, the technique of filling with a single cone associated with the endodontic sealer was used. The presence of three root canals in premolars has a low prevalence, however, it is extremely important for the professional to know about the possible anatomical variations, since this can influence the success of endodontic treatment. Given the limitations, the correct management of these cases can be attributed to a good radiographic evaluation, the use of magnification and clinical criteria that, together, helped to obtain the best possible result.